High resolution mapping in the major histocompatibility complex region identifies multiple independent novel loci for psoriatic arthritis. Issue 4 (17th January 2011) - Rahman, Proton; Roslin, Nicole M; Pellett, Fawnda J; Lemire, Mathieu; Greenwood, Celia M T; Beyene, Joseph; Pope, Angela; Peddle, Lynette; Paterson, Andrew D; Uddin, Mohammed; Gladman, Dafna D
Abstract : Objective: Psoriatic arthritis (PsA) has a clear familial predisposition, the major histocompatibility complex (MHC) region being the strongest genetic locus. The study primary objective was to identify single nucleotide polymorphisms (SNPs) independent of known human leucocyte antigen (HLA) alleles within the MHC region that are associated with PsA using a high-density SNP map. Method: In all, 914 samples were assessed, including 427 PsA cases from 2 well established PsA cohorts and 487 controls from Canada. The genotype data consisted of 2521 SNPs from 2 Illumina Goldengate MHC panels, spanning 4.9 Mb of chromosome 6 with an average spacing of 2 kb. Classical HLA alleles were genotyped in all subjects using sequence-specific oligonucleotide probes or sequence-specific primers. A conditioning approach was used to distinguish between new associations and those in linkage disequilibrium (LD) with known HLA alleles. Results: Unconditional association analysis revealed 43 markers with p<7.26×10 −5 (calculated experiment-wide significance threshold). In the conditional analysis, 10 SNPs showed statistically significant association at a threshold of p<7.26×10 −5 . Seven SNPs were in strong LD in the study data (pairwise r 2 >0.77 in the controls) reflecting one association signal. These SNPs spanned a 1.6 Mb region. SNP rs1150735 is 1.5 kb upstream from ring finger protein 39 (RNF39). RNF39 SNPs have been associated with HIV1 disease progression and set point CD4 T cell count. Conclusion: Four new loci for either psoriasis or PsA in the MHC region that are independent of known HLA alleles have been identified. The effect size of these variants is modest. Replication of these variants in multiple larger populations is necessary.